Child-Friendly Islamic Boarding Schools: A Conceptual Study of Islamic Education Strategies in the Prevention of Violence Against Children - Hasibuan, Nurman (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
Pesantren as the oldest Islamic educational institution in Indonesia has a strategic role in shaping the character, morals, and personality of students. Therefore, Islamic boarding schools have a great responsibility in ensuring the fulfillment of children's rights, including the right to a sense of security, protection from violence, and a healthy and inclusive learning environment. The purpose of this research is to explore, analyze, and systematize various literature, both from classical and contemporary sources, that discuss child protection, education management, and Islamic values that are relevant in building a safe, inclusive, and well-oriented educational environment for students. The research method used is a qualitative method with a library research approach using descriptive-analytical analysis, through the review of literature in the form of books, journals, scientific articles, and policy documents related to the concept of child-friendly education that is not inseparable from the leadership of kiai and teachers, internal regulations in the form of codes of ethics and discipline, parental involvement, and healthy spatial design.  is an important element in creating a conducive pesantren climate. As a literature research, this study makes a conceptual contribution in enriching the academic discourse on child-friendly pesantren as well as being a normative reference for the development of child-friendly pesantren policies.